The Used Of Flash Card To Increase The Autistic Student Interaction In Simple Speaking - Mardalena, Rilta; Tohar, Ahmaddin Ahmad; Lestari, Yuliana Intan (Universitas Negeri Surabaya, 2025)
Background: The students difficulties to make interaction with their teacher in the classroom, The process of teaching new vocabulary by using flash card. Objective: To know the autistic students in interaction, and the student’s response to it thus making the learning process easier. Methode: The writer conducted Classroom Action Research (CAR) which consists of two cycles, each cycle consists of four elements, namely: planning, acting, observing and reflecting. The writer doing the observation about January to March. Result: the students can implementation their vocabulary in simple speaking, the students have good eye contact, at the studied, the students can focus and giving good attention, the students can make good appropriate play with peers. The autistic students have a good dialog in simple speaking, and they can make minimal five different sentence of the some word who know. Conclution: The problem in the cycle is usually the students got difficulty to memorize the words and they easily get bored in studying English. To answer the problems the writer uses flash card to increase the student’s vocabulary. Abstrak Latar Belakang: Kesulitan siswa dalam berinteraksi dengan guru di kelas, Proses pengajaran kosakata baru dengan menggunakan flash card. Tujuan: Untuk mengetahui siswa autis dalam berinteraksi, dan respon siswa terhadapnya sehingga membuat proses pembelajaran lebih mudah. Metode: Penulis melakukan Penelitian Tindakan Kelas (PTK) yang terdiri dari dua siklus, setiap siklus terdiri dari empat elemen, yaitu: perencanaan, tindakan, pengamatan dan refleksi. Penulis melakukan observasi sekitar bulan Januari sampai Maret. Hasil: siswa dapat mengimplementasikan kosakata mereka dalam berbicara sederhana, siswa memiliki kontak mata yang baik, pada saat belajar, siswa dapat fokus dan memberikan perhatian yang baik, siswa dapat melakukan permainan yang tepat dengan teman sebaya. Siswa autis memiliki dialog yang baik dalam berbicara sederhana, dan mereka dapat membuat minimal lima kalimat yang berbeda dari beberapa kata yang mereka ketahui. Kesimpulan: Masalah dalam siklus ini biasanya siswa mengalami kesulitan untuk menghafal kata-kata dan mereka mudah bosan dalam belajar bahasa Inggris. Untuk menjawab masalah tersebut penulis menggunakan flash card untuk meningkatkan kosakata siswa.